La blockchain au service de la question sociétale : étude de ses fonctions en droit de la responsabilité sociétale des entreprises - Arrouas, David (Université de Strasbourg, 2024)
La blockchain à travers ses fonctions registres et smart contracts constitue un moteur de la confiance. Le registre blockchain, distribué sécurisé et sans autorité centrale, révolutionne la confiance. Le smart contract, adossé à une blockchain, auto-exécutant et inaltérable assure, lui, l'exécution automatique d'actions prédéfinies. Initialement conçus pour le secteur financier, le potentiel de cette technologie s’étend à la RSE en tant que support de la norme. Les smart social contracts seraient en mesure d’automatiser les processus liés à la RSE, tandis que le registre blockchain renforcerait la transparence et la traçabilité. Un cadre juridique clair reste cependant essentiel pour concilier innovation et protection des droits. Définir le rôle de la blockchain dans une démarche de RSE pourrait transformer les interactions des entreprises avec leurs parties prenantes, renforcer la confiance, la transparence, la réactivité et, plus largement, l’effectivité de norme sociétale.
Keywords: Blockchain; Blockchains; CSR; Confiance; Devoir de vigilance; Duty of vigilance; RSE; Responsabilité Sociétale de l'Entreprise; Smart contract; Smart social contract; Trust

Les entreprises multinationales et les normes internationales de responsabilité sociale des entreprises - Aerts, Lisa (Université Paris 1, 2024)
Qu’elles soient considérées comme des alliées ou des concurrentes des États, employeurs des citoyens ou sources d’incidences négatives sur leur environnement, le rôle des entreprises multinationales dans l’ordre juridique international est indéniable. La sphère internationale s’est, bien que difficilement, progressivement munie de normes enjoignant aux entreprises multinationales de respecter un certain nombre de droits, parmi lesquels les Principes directeurs de l’OCDE, les Principes directeurs de l’ONU, le Pacte mondial, la Déclaration tripartite de l’OIT, et l’ISO 26 000. Cependant, le statut et la nature de ces entités transnationales, couplés à une économie libérale encline à ne pas freiner l’activité économique, ne permettent pas d’imposer ces standards et relèvent de prime abord de la soft law. Il a donc fallu faire appel au sujet de ces normes pour qu’elles soient diffusées tout au long de leurs chaînes de production. Ainsi, par stratégie, par philosophie gestionnaire ou, comme le clament certaines, par humanisme, les entreprises multinationales se sont graduellement dotées de codes de conduite d’entreprises ou à l’intention de leurs fournisseurs, et ont négocié des accords-cadres mondiaux s’appuyant sur les normes internationales. Cette étude porte sur la réalité de l’influence du droit international sur le contenu de ces instruments privés. Ces derniers, bien que volontairement élaborés, peuvent être des pistes et des atouts pour une responsabilité sociale des entreprises plus pertinente, cohérente et effective. S’appuyant sur un corpus de 138 codes de conduite et accords-cadres, ainsi que l’ensemble des Accords du Rana Plaza, cette recherche tend à identifier les textes internationaux dont se saisissent les entreprises et ceux qu’elles évitent, les droits et devoirs qu’elles s’engagent à respecter et ceux qu’elles semblent vouloir ignorer, ainsi que les conséquences de ces arbitrages. Les normes internationales encouragent également les entreprises à mettre en place des processus dans l’élaboration, l’application et la vérification de leurs engagements tels que la due diligence, ou la transparence ainsi que la prise en compte des parties prenantes. Là encore, les entités économiques opèrent de différentes manières plus ou moins proches des attendus internationaux. L’analyse de ces instruments privés de RSE, le rôle des multiples acteurs internationaux dans leur déploiement — dont l’État —, et leur respect ou non du droit international, soulignent des pistes de contrainte et de possible durcissement du droit international pour aboutir à une responsabilité sociale des entreprises multinationales réellement transnationale et aux résultats plus probants. Whether they are considered allies or competitors of States, employers of citizens or sources of negative environmental impact, the role of multinational companies in the international legal order is undeniable. The international sphere has, with some difficulties, gradually equipped itself with standards requiring multinational companies to respect a number of rights, including the OECD Guidelines, the UN Guiding Principles, the Global Compact, the ILO Tripartite Declaration and ISO 26000. However, the status and nature of these transnational entities, coupled with a liberal economy inclined not to curb economic activity, do not allow these standards to be imposed, and are at first sight a matter of soft law. It was therefore necessary to appeal to the subject of these standards for them to be applied throughout their supply chains. Thus, as a matter of strategy, management philosophy or, as some claim, humanism, multinational companies have gradually adopted corporate codes of conduct or codes of conduct for their suppliers, and negotiated global framework agreements based on international standards. This study examines the influence of international law on the content of these private instruments. The latter, though deliberately elaborate, can be a path to more relevant, coherent and effective corporate social responsibility. Based on a corpus of 138 codes of conduct and framework agreements, as well as the Rana Plaza Accords, this research aims to identify the international texts that companies take up and those they avoid, the rights and duties they undertake to respect and those they appear to ignore, and the consequences of those choices. International standards also encourage companies to set up processes for drawing up, applying and verifying their commitments, such as due diligence process, transparency and stakeholder involvement. Here again, economic entities operate in a variety of ways, more or less in line with international expectations. An analysis of these private instruments, the role of the many international players involved in their deployment - including the States - and whether or not they comply with international law, highlights possible avenues of constraint and possible tightening of international law to achieve more effective transnational corporate social responsibility.
Issue: 2024PA01D060
Keywords: Accords-cadres mondiaux; Codes de conduite; Codes of conduct; Entreprises multinationales; Global Compact; Global framework agreemen; ILO; Multinational companies; OCDE; OECD; OIT; ONU; Pacte mondial; Rana Plaza; UN

Corporate Social Responsibility Practices in the Nigerian Public Sector - Mohammed, Abbas (University of Plymouth, 2024)
This study examines Corporate Social Responsibility (CSR) practices in Nigerian public sector organisations using a comprehensive mixed-methods approach. The data collection process involved analysing 185 organisation-year observations from annual reports spanning 2011–2020, as well as questionnaires distributed to key stakeholders and interviews with senior executives from various organisations.The analysis utilised a multi-pronged strategy, including quantitative techniques such as regression analysis to explore the relationship between CSR practices and corporate governance mechanisms and qualitative methods such as narrative analysis and thematic coding to gain insights from survey responses and interviews.The findings indicate that CSR practices in the Nigerian public sector are moving in a positive direction. Organisations demonstrated commitment to CSR activities, including community development, education, environmental conservation, and philanthropy. Survey results showed that 83% of organisations engaged in CSR, driven by community acceptance and moral obligation. Additionally, 84% of organisations complied with regulatory frameworks, and 79% aligned their CSR policies with national or international standards. The analysis also found a significant positive relationship between CSR practices and factors such as larger board sizes, greater board independence, the presence of women on the board, and CEOs with longer tenures, higher educational qualifications, and international exposure.By triangulating these findings, it is clear that organisations have a strong commitment to giving back through various CSR initiatives, such as humanitarian assistance, youth empowerment, and educational programmes. Despite challenges such as budgetary constraints and weak accountability frameworks, organisations recognise the perceived benefits of CSR, including increased public confidence, improved stakeholder perceptions, enhanced organisational reputation, trust-building, community engagement, and empowering marginalised communities through education.The insights gained from this study conducted in an emerging economy namely, Nigeria, provide a new understanding of CSR practices in public-sector organisations. They also highlight the proactive approach of public sector organisations towards responsible practices. Consequently, the implications of this research extend beyond national boundaries, encouraging diverse and dedicated leadership to enhance CSR efforts and create lasting social impact. Future studies could explore comparative analysis between the public and private sectors or different countries, as well as sector-specific impact assessments.
Keywords: CSR; Corporate Social Responsibility; ESG; Sustainability

A responsabilidade das empresas transnacionais na preservação dos direitos indígenas - Alves, Alessandra Vanessa (Universidade Nove de Julho, 2024)
The present study aimed to identify the duties – expressed and implicit – that arise for transnational companies when their economic activities are conducted on indigenous lands or have an impact on them. To this end, identified the most recurrent violations of indigenous peoples' interests regarding the commercial exploitation of their lands or surroundings. Adopting the context of the Krenak people, it was identified that the Krenak, similar to other indigenous peoples, have experienced conflicts on multiple fronts due to large scale projects affecting their territoriality, access to natural resources (with prejudice to their subsistence), and their very way of life and existence. Reflecting on the commitment made to by political entities and their respective branches with the enactment of the Federal Constitution of 1988, the constitutional provisions were interpreted from a historical perspective. It was identified that economic exploitation of indigenous lands -contingent upon legislation - shall, if enacted (because it is not a constitutional duty but a mere possibility), adhere to the criteria previously outlined in the Constitution, including consultation with the peoples concerned, authorization by the National Congress, and the right to participate in the results of the extraction. Furthermore, the principles derived from these criteria include the exceptional nature of exploration, preservation of indigenous wealth - both material and immaterial - and recognition of indigenous thought as a decisive element. It was concluded that these principles entail an extensive list of duties for transnational companies concerning indigenous peoples, which must be implemented with consideration for indigenous worldviews - an underlying assumption for the application of indigenous rights. This list is not static; rather, it should evolve with human rights developments and ensure the ability to address new challenges arising from the relationship between transnational companies and indigenous peoples.
Accepted: 2024-09-11T17:42:54Z
Keywords: CSR; RSE; Responsabilidad Social; Responsabilité sociale de l'entreprise

Entreprises et droit international humanitaire - Pizzetta, Scarlett (Université Côte d'Azur, 2024)
La mondialisation de l'économie de marché ouvre de nouveaux horizons aux entreprises commerciales en étant source de croissance, d'emplois et de prospérité, même si elle engendre aussi des risques, en particulier lorsque les entreprises développent des activités dans des zones en proie à des conflits armés, internationaux ou internes, ou dans des territoires occupés. Les entreprises sont incitées par la société civile et les organisations internationales à tenir de plus en plus compte du droit relatif aux droits de l'homme, qui s'applique tant en période de conflit armé que de paix. Le droit international humanitaire, alors même qu'il est spécifiquement conçu pour régir des situations de conflit armé, qu'il a des effets importants pour elles lorsqu'elles opèrent dans des pays qui connaissent de telles situations, leur est moins connu et fait moins l'objet d'attention par la doctrine, notamment francophone.Un certain nombre de contentieux récents ont soulevé des interrogations en la matière, tant sur le plan de la protection des entreprises par le corpus du droit international humanitaire, que sur celui de la soumission des entreprises à ces règles. Cette thèse analyse l'applicabilité du droit international humanitaire aux entreprises commerciales, à leurs salariés, leurs biens, leurs activités qui peuvent être à la fois des cibles, des victimes, des participants des conflits armés, voire des auteurs de violations du droit international humanitaire, soulevant des interrogations relatives à l'adaptation et la pertinence du DIH à ces entités.
Keywords: Business Enterprises; Criminal and civil liability; Droit humanitaire; Droit international humanitaire; Droits et protections; Entreprises – Droit; Entreprises commerciales; International humanitarian law; Obligations and risks; Obligations et risques; Personnes morale (responsabilité); Personnes morales (responsabilité pénale); Responsabilité civile et pénale; Rights and protections; Victimes et acteurs des conflits armés; Victims and actors of armed conflicts

A companhia engajada : disciplina dos atos societários de orientação social - Galizzi, Gustavo Oliva (Universidade de São Paulo, 2024)
Os acadêmicos divergem desde sempre a respeito do objetivo da companhia: atender ao interesse dos acionistas e buscar a maximização dos resultados ou, alternativa ou sucessivamente, atender ao interesse de outras partes interessadas? Porém, as linhas entre uma e outra correntes não são mais nítidas como antes. Com o crescente interesse nas chamadas métricas de ESG a sigla para Environmental, Social and Governance, modelos híbridos de governança têm sido pensados a partir da combinação de lucro e propósito. Nesse sentido parece evidente a consolidação de uma tendência no direito societário que, por falta de um termo melhor, possa ser qualificada como preponderantemente social. Sem prejuízo dessa evidência, o objetivo do trabalho não é o de defender uma ou outra corrente sobre a função da companhia. Num olhar pretensamente original, o estudo propõe outro enfoque: traçar a disciplina legal dos atos societários de orientação social, como materialização do interesse que os precede. Academics have always disagreed about the company\'s objective: to serve the interests of shareholders and seek to maximize results or, alternatively or successively, to serve the interests of stakeholders as other interested parties? However, the lines between one theory and another are no longer as clear as before. With the growing interest in the so-called ESG metrics the acronym for Environmental, Social and Governance, hybrid governance models are being designed based on the combination of profit and purpose. The consolidation of a trend in corporate law that, for lack of a better term, can be qualified as predominantly social is now clear. Notwithstanding the before, the objective of the study is not to defend one or another theory of the corporate objective. In an allegedly original perspective, the study proposes another approach: tracing the legal discipline of socially oriented corporate acts, as the externalization of the interest that precedes them.
Keywords: Atos societários de orientação social; Corporate objective; Corporate purpose; ESG; Interesse social; Propósito social; Socially oriented corporate acts